Power Optimization between sensing and signaling for Distributed Detection - Xiangyang LIU; Peisheng ZHU; Donghong XIE (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The power of each sensor node in wireless sensor networks for signal detection applications is scarce and limited. Thus, the allocation of power resource of a node should make the detection performance of the whole network maximum, which is complex due to the detection probability of the whole system cannot be expressed explicitly. The ant colony optimization algorithm is good at solving multidimensional optimization problem. Consequently, continuous ant colony system (CACS) and ACOR proposed in literature are adopted to optimize the allocation of node’s power between sensing and communications. Simulation show that they can lead to a good power allocation. Meanwhile, the identical power allocation scheme (IPAS) that all sensor nodes have identical power assignment can achieve nearly the same detection performance as that achieved by the best scheme searched by CACS and ACOR. As a result, particularly for a large number of identical sensors, IPAS can be employed to achieve nearly the best detection performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3032